ajom 2021
DOI: 10.5943/ajom/4/1/8
|View full text |Cite
|
Sign up to set email alerts
|

AJOM new records and collections of fungi: 101-150

Abstract: This article is the second in the Asian Journal of Mycology Notes series, wherein we report 50 new fungal collections distributed in two phyla, six classes, 23 orders and 38 families. The present study provides descriptions and illustrations for three new species (Acolium yunnanense, Muyocopron cinnamomi and Thyrostroma ulmeum), 44 new host records and new geographical distributions and three new reference collections. All these introductions are supported by morphological data as well as the multi-gene phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…To date, eight species of microfungi on Dipterocarpaceae have been described from Thailand, viz. Hermatomyces thailandica, Lauriomyces sakaeratensis, Lembosia xyliae, Pseudoplagiostoma dipterocarpi, P. dipterocarpicola, Pestalotiopsis shoreae, Pulvinaticonidioma hyalinum, and Subellipsoidispora guttulata (Suwannarach et al, 2016;Chethana et al, 2021b;Farr and Rossman, 2022;Tang et al, 2022; This study). Among these species, Pseudoplagiostoma dipterocarpi is an endophyte, while the rest are saprobes.…”
Section: Discussionmentioning
confidence: 78%
“…To date, eight species of microfungi on Dipterocarpaceae have been described from Thailand, viz. Hermatomyces thailandica, Lauriomyces sakaeratensis, Lembosia xyliae, Pseudoplagiostoma dipterocarpi, P. dipterocarpicola, Pestalotiopsis shoreae, Pulvinaticonidioma hyalinum, and Subellipsoidispora guttulata (Suwannarach et al, 2016;Chethana et al, 2021b;Farr and Rossman, 2022;Tang et al, 2022; This study). Among these species, Pseudoplagiostoma dipterocarpi is an endophyte, while the rest are saprobes.…”
Section: Discussionmentioning
confidence: 78%
“…In this study, we reported three strains of P. capitalensis from three different hosts. Phyllosticta capitalensis is the most commonly isolated endophytic species in the genus and is widely distributed (Chethana et al 2021d;Manawasinghe et al 2022). Therefore, it is important to study this group of fungi.…”
Section: Genealogical Concordance Phylogenetic Species Recognition An...mentioning
confidence: 99%